2020
DOI: 10.1007/s00330-020-07399-z
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of left atrial function using cardiac magnetic resonance imaging

Abstract: Objectives To determine the test-retest reproducibility and observer variability of CMR-derived LA function, using (i) LA strain (LAS) and strain rate (LASR), and (ii) LA volumes (LAV) and emptying fraction (LAEF). Methods Sixty participants with and without cardiovascular disease (aortic stenosis (AS) (n = 16), type 2 diabetes (T2D) (n = 28), end-stage renal disease on haemodialysis (n = 10) and healthy volunteers (n = 6)) underwent two separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…Studies evaluating the test–retest reproducibility of LA assessment have been limited and with small sample sizes (n = 12–22) and mainly in healthy volunteers [ 40 , 67 , 100 , 101 ] (Table 4 ). However, a recent study including subjects with and without cardiovascular disease (n = 60) showed LAEF to have better test–retest reproducibility than LA strain, whilst reservoir strain accounted for the most reproducible strain parameter [ 102 ].…”
Section: Reproducibility Of Techniquesmentioning
confidence: 99%
“…Studies evaluating the test–retest reproducibility of LA assessment have been limited and with small sample sizes (n = 12–22) and mainly in healthy volunteers [ 40 , 67 , 100 , 101 ] (Table 4 ). However, a recent study including subjects with and without cardiovascular disease (n = 60) showed LAEF to have better test–retest reproducibility than LA strain, whilst reservoir strain accounted for the most reproducible strain parameter [ 102 ].…”
Section: Reproducibility Of Techniquesmentioning
confidence: 99%
“…Our study showed the same results. However, Alfuhied A et al 40 found that sixty participants including 16 aortic stenosis, 28 type 2 diabetes, 10 end‐stage renal disease on hemodialysis, and 10 healthy volunteers underwent CMR scans, the result showed that LA strain and strain rate assessment using CMR‐FT showed moderate to poor test–retest reproducibility across disease states, LAV and emptying fraction showed more reproducible on CMR. It may be related to the small number and heterogeneous of disease in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ferreira et al have shown that defective LA emptying fraction was a strong predictor for all-cause mortality [35].As for LA strain, studies have shown that LA strain was related to LV dysfunction and AS severity, being also an independent predictor for HF hospitalization, all-cause mortality, and new-onset atrial brillation, regardless of LA dilation [36,37]. Recently, Kim et al have conducted a CMR study in which they have suggested that LA peak longitudinal strain might predict cardiovascular events in AS [38], but several studies have shown that traditional CMR methods might have questionable reliability, requiring further adjustments [39]. Taken together, more work is still required to properly assess the prognosis ability of CMR-based LA parameters.…”
Section: Discussionmentioning
confidence: 99%